A nationally representative cross‐sectional survey on health information access for consumers in Japan: A protocol for the INFORM Study. Issue 2 (28th April 2022) - Otsuki, Aki; Saito, Junko; Yaguchi‐Saito, Akiko; Odawara, Miyuki; Fujimori, Maiko; Hayakawa, Masayo; Katanoda, Kota; Matsuda, Tomohiro; Matsuoka, Yutaka J.; Takahashi, Hirokazu; Takahashi, Miyako; Inoue, Manami; et al.
Abstract: In Japan, risk behaviors for cancer remain inadequately controlled, often due to a lack of necessary information and support to guide consumers in cancer control decisions. The use of strategic health communication efforts based on social marketing has substantial potential to provide groups of consumers who are underinformed or misinformed with relevant cancer information, both to reinforce their cancer awareness, knowledge, attitudes, and beliefs and to strengthen behaviors to prevent cancer. The INFORM Study monitors these variables nationally and identifies populations most in need of cancer‐related information. A nationally representative cross‐sectional mail survey was used to investigate consumer behaviors related to cancer prevention and screening, as well as cancer knowledge, attitudes and beliefs, and access to and use of trusted cancer information. A total of 10, 000 Japanese aged 20 years or older were selected by two‐stage stratified random sampling. The self‐administered questionnaire consisted of core items from the Health Information National Trends Survey in the United States with some additional items not covered in HINTS but important in Japan. This national survey is expected to play an important role in promoting effective dissemination of evidence‐based recommendations. Key points: 1. This is the first nationwide survey of cancer control in Japan to monitor communication channel, personal characteristics such as knowledge and attitude, behavioral characteristics, socioeconomic and geographical characteristics. 2. We identify the populations who are in most need of cancer‐related information and their access to and use of cancer information, and provide the basis for tailoring of messages to each segmented group's needs and interests. 3. This national survey can play an important role in promoting effective dissemination of evidence‐based recommendations and implementation of evidence‐based interventions to prevent cancer.